Adverse Event Profile Associated with Prolonged Use of CentriMag Ventricular Assist Device for Refractory Cardiogenic Shock. Issue 8 (November 2019) - Cevasco, Marisa R.; Li, Boyangzi; Han, Jiho; Chiuzan, Codruta; Mauro, Christine M.; Kurlansky, Paul; Garan, A. Reshad; Takeda, Koji; Naka, Yoshifumi; Takayama, Hiroo
Abstract : Several studies have investigated early outcomes with a surgical short-term ventricular assist device (VAD), but little is known about adverse event profile during prolonged support with a surgical short-term VAD. This is a retrospective analysis of 161 patients who received a CentriMag ventricular assist system (Abbott Laboratories, Abbott Park, IL) at our institution between January 2007 and June 2014. Device-related adverse events include major bleeding, infection, and stroke incidents occurring during CentriMag support. Cumulative frequency of adverse events was estimated by Nelson's nonparametric method. One hundred and forty-three (88.8%) patients had biventricular VAD and 18 (11.2%) had isolated left VAD. Median duration of support was 16 days (interquartile range [IQR]: 10–29). Mortality was 24.8% and 1 year overall survival is 51.8% (95% CI: 43.3–59.5%). The most common adverse event during support was major bleeding (n = 121, 75.1%). Ninety-five (59.0%) developed major infections such as pneumonia and urinary tract infection. Sixteen patients (10%) experienced stroke. Cumulative data analysis showed that stroke and reoperation caused by bleeding were rare beyond 30 days, whereas infection and nonsurgical bleeding events were directly related to support time. In conclusion, temporary VAD with CentriMag support is an effective treatment for patients in refractory cardiogenic shock. Despite its side effect, profile including a high rate of blood transfusion early in the immediate postoperative period of CentriMag support, aggressive use of the CentriMag support device has acceptable survival to discharge and 1 year survival. Abstract : Supplemental Digital Content is available in the text.